Ngentep Penjaga Mahkota: Menghidupkan Permainan Tradisional sebagai Media Edukasi Anak-anak di Desa Ngentep Magetan - Endang Sri Maruti; Pujiady, Esa Nugraha Fatharina; Arrizal, Nizam Zakka; Riyanto, Yeri Dedi (Innovative Journal of Community Engagement, 2025)
Traditional games are part of our cultural heritage and hold significant educational value, particularly in shaping children's character. However, rapid technological advancements have shifted children's attention to digital games, leading to reduced social interaction and increased use of profanity in everyday communication. This activity seeks to implement the traditional game NPM (Ngentep Mahkota Jaga), a modification of Gobak Sodor, with additional rules prohibiting profanity and a bonus point system. This activity aims to enhance social interaction and reduce dependence on mobile phones among children. This activity was conducted with children from Ngentep Village participating in an NPM competition. The results showed that this game increased children's awareness of the importance of polite communication, fostered camaraderie, and reduced the intensity of mobile phone use during play. Thus, traditional games can be an effective educational alternative for shaping children's character in the digital age.